Temporal characterization of ventricular function and deformation after Takotsubo syndrome using cardiovascular magnetic resonance imaging. (13th July 2021) - Marques Pires, C; Passos, RM; Medeiros, P; Oliveira, C; Flores, R; Mane, F; Silva, R; Antunes, N; Vieira, C; Queiros, S; Pereira, VH
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: The time course of ventricular recovery in Takotsubo Syndrome (TS) patients(pts) is still not well characterized. Quantification of myocardial deformation using Cardiovascular Magnetic Resonance Feature-Tracking (CMR-FT) may be a useful method to better characterize ventricular recovery during TS. AIM: To assess the time course of ventricular function using CMR-FT myocardial strain in patients (pts) with an episode of TS. METHODS: We performed a single-center, retrospective cohort study including 130 pts admitted with TS over a 10-year period. From this cohort, 39 (30%) pts were selected and age and sex-matched with 16 healthy controls for a comparative analysis of myocardial strain using CMR-FT. TS pts were divided in 3 homogeneous subgroups according to the time from index-event and the CMR acquisition: Group 1(G1): <8 days; Group 2(G2): 8 to 30 days; Group 3 (G3): >30 days. One operator blinded for the study group performed the analysis. Left ventricle (LV) radial strain (RS), longitudinal strain (LS) and right ventricle (RV) LS were quantified. RESULTS: The mean age of TS group was 66 years and 90% were female. The median ejection fraction (EF) at admission was 38%; 82% displayed an apical ballooning (AB) pattern. Around 19% had at least 1 in-hospital complication and 1.5% died during hospitalization. A significant increase use of CMR was observed over the years (p = 0.001). Myocardial deformation analysis showed a significant group interaction for LV LS and RS. Specifically, the global values of G1 LV LS and RS were significantly decreased when compared with G3 (LS:-15vs-20%;p = 0.002; RS:40vs61%; p < 0.001) and controls (LS:-15vs-22%;p < 0.001; RS: 40vs70; p < 0.001). There were no significant differences in the RV LS across groups. The CMR-quantified EF was significantly decreased in G1 when compared with G3 (52vs64%; p < 0.003) and controls (52vs64%; p < 0.001). Differences between G1 and G2 were found in LV RS (LS:40vs57%; p < 0.001) and EF (52vs62%; p < 0.001). No differences were observed for any parameters between G3 and controls. This study showed that global LV LS (r=-0.6, p < 0.001) and RS (r = 0.7, p < 0.001) had a significant correlation with the CMR-quantified EF. A comparison between the different patterns of TS was also performed (Figure 1). Pts with AB pattern in G1 displayed lower global RS (P = 0.014), although there were no differences regarding global LS. As expected, in the AB group the reduction in myocardial strain was limited to the apical segments. Despite not being significantly different across groups RV LS was the only CMR-derived predictor of complications during follow-up (OR = 1.17; p = 0.026). CONCLUSION: This study revealed that after an episode of TS myocardial function quantified either by EF or CMR-FT strain fully recovers between the 8th and 30th day of the event. RV strain was a predictor of complications during follow-up.